Enriched English instructional broadcast for grade two fast learners - Tabacug, Julieta Ybañez 1942- (1973)
The main purpose of the study is to present an enriched English instructional broadcast as an adjunct to Language Arts teaching for Grade Two fast learners. The study is an enrichment of thirty-five English broadcast lessons with the regular broadcasts as its point of reference. It is to be used as an adjunct in the teaching of Language Arts to Grade Two fast learners in the hope of heightening the child's enthusiasm to learn more and discover hinself, and gain wide range of experiences. The radio plays and dramas found at the appendix are recommended for children's theatre presentation.